2017
DOI: 10.1007/s00127-017-1367-z
|View full text |Cite
|
Sign up to set email alerts
|

Suicide rates in European OECD nations converged during the period 1990–2010

Abstract: The study indicates that beta convergence alone explained most of the cross-national variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The overall suicide rates declined between 1979 and 2016. This was consistent with worldwide trends (Bremberg, 2017;WHO, 2019) with the exception of data from the region of the Americas. The global data could be related to higher attention being paid to mental health through the development of suicide prevention programs (Fond et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The overall suicide rates declined between 1979 and 2016. This was consistent with worldwide trends (Bremberg, 2017;WHO, 2019) with the exception of data from the region of the Americas. The global data could be related to higher attention being paid to mental health through the development of suicide prevention programs (Fond et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Sixth, the current review found that suicide rates overall were not significantly associated with the included indices of economic quality and inequality. Although ours is not the only study to find that economic indices did not significantly relate to suicide rates (Bremberg, 2017;Vijayakumar, Nagaraj, Pirkis, & Whiteford, 2005), this finding is somewhat surprising in light of converging evidence, suggesting that economic factors have a significant impact on suicidal behavior (Bachmann, 2018). For instance, economic crises, and high unemployment rates in particular (Nordt, Warnke, Seifritz, & Kawohl, 2015), have been broadly linked to suicide deaths (WHO, 2014).…”
Section: (B) Malesmentioning
confidence: 72%
“…Most studies in the literature were performed in three main countries (ie, the United States, the United Kingdom and Canada) more than 10 years ago and included small samples of trainees (Leaune et al 2019). Given the discrepancies between suicide rates (Bremberg, 2017) and psychiatric training (Kuzman et al, 2012) across countries, the decline in suicide rates in recent years in Europe (Bremberg, 2017) and recent modifications in psychiatric training programmes (Steiner, Giggie, Koh, Mangurian, & Ranz, 2014), new research on the topic is needed. More knowledge is needed to propose guidelines promoting the early detection of trainees who show the greatest risk for being strongly impacted by PS.…”
mentioning
confidence: 99%